Suspicion and treatment of severe sepsis. An overview of the prehospital chain of care - Herlitz, Johan (BioMed Central, 2012)
BACKGROUND: Sepsis is a life-threatening condition where the risk of death has been reported to be even higher than that associated with the major complications of atherosclerosis, i.e. myocardial infarction and stroke. In all three conditions, early treatment could limit organ dysfunction and thereby improve the prognosis. AIM: To describe what has been published in the literature a/ with regard to the association between delay until start of treatment and outcome in sepsis with the emphasis on the pre-hospital phase and b/ to present published data and the opportunity to improve various links in the pre-hospital chain of care in sepsis. METHODS: A literature search was performed on the PubMed, Embase (Ovid SP) and Cochrane Library databases. RESULTS: In overall terms, we found a small number of articles (n = 12 of 1,162 unique hits) which addressed the prehospital phase. For each hour of delay until the start of antibiotics, the prognosis appeared to become worse. However, there was no evidence that prehospital treatment improved the prognosis. Studies indicated that about half of the patients with severe sepsis used the emergency medical service (EMS) for transport to hospital. Patients who used the EMS experienced a shorter delay to treatment with antibiotics and the start of early goal-directed therapy (EGDT). Among EMS-transported patients, those in whom the EMS staff already suspected sepsis at the scene had a shorter delay to treatment with antibiotics and the start of EGDT. There are insufficient data on other links in the prehospital chain of care, i.e. patients, bystanders and dispatchers. CONCLUSION: Severe sepsis is a life-threatening condition. Previous studies suggest that, with every hour of delay until the start of antibiotics, the prognosis deteriorates. About half of the patients use the EMS. We need to know more about the present situation with regard to the different links in the prehospital chain of care in sepsis.